Peripheral venous or tibial intraosseous access for medical emergency treatment in the dental office? - Goldschalt, Christin; Doll, Sara; Ihle, Brit; Kirsch, Joachim; Mutzbauer, Till Sebastian (British dental journal, 2015)
Background: The anterior tibia has been recommended as emergency vascular access site if the intravenous route cannot be used. Objective: This study aims to evaluate the peripheral venous and anterior tibial intraosseous puncture as alternatives for dentists, using a human and a cadaver model. Method: One group of dental students performed a venipuncture by using a standard catheter device (n = 21) on other students. Another group (n = 24) used the Vidacare EZ-IO intraosseous kit on a cadaver tibia with india ink as a tracer. Success rates as well as the time needed for a successful puncture were recorded. Results: 28.5% of venous and 83.3% of intraosseous punctures were successful. The relative risk of venous cannulation failure was 3.4 (95% CI 1.6–7.2; p = 0.0005). A successful venous access could be performed within 163 ± 23.2 seconds (mean ± SD), a tibial intraosseous access within 30 ± 27.8 seconds (p = 0.0003). Conclusions: Within the limitation of this study, it can be demonstrated that the chances to perform a successful vascular access for inexperienced dentists may be higher when using the tibial intraosseous route for emergency intravascular medication.
Gesehen am 20.07.2020